Teachers' perception of administrators support towards the integration of laptops in schools: an exploratory study - Moses, Priscilla; Wong, Su Luan (Faculty of Educational Studies, Universiti Putra Malaysia, 2010)
The Malaysian Ministry of Education granted each Mathematics and Science teacher with a laptop. The integration of laptop needs strong support from the school administrators to successfully implement it. Therefore, this quantitative study was carried out to explore how teachers perceived the support of administrators in the integration of laptops in the teaching-learning process. Respondents were 38 secondary school teachers from the state of Selangor, Malaysia. The overall perception of the teachers on the administrators support was reported as satisfying. More than half of the teachers (56.5%) agreed that they received administrators support in integrating the laptops in the teaching-learning process and only a small percentage of the teachers (17.5%) disagreed that they received adequate support by the administrators.